1837-1838 Tenn. Pub. Acts 201, ch. 137, § 4 - (:unkn) unknown (General Publisher, 1837)
Prohibited the stabbing or cutting of another person with any knife or weapon known as a “Bowie knife, Arkansas tooth pick, or any knife or weapon that shall in form, shape or size resemble a Bowie knife,” regardless of whether the person dies. Punishable by imprisonment for 3-15 years.
--
Keywords: COMMITTING CRIME W/ WEAPON - NON-GUN ARMS